Liothrips species (Thysanoptera, Phlaeothripinae) from leaf-galls on Piper species in Southeast Asia and Australia - Mound, Laurence A. (Zootaxa, 2020)
Variation in colour and structure is re-considered amongst 19 species of Liothrips collected from leaf-galls on Piper vines in Asia. Gynaikothrips crassipes Karny, Liothrips aemulans Priesner, and Liothrips baccati Priesner are considered new synonyms of Liothrips chavicae (Zimmermann). Gynaikothrips karnyi Bagnall is considered a new synonym of Liothrips mirabilis (Schmutz). Gynaikothrips kuwanai Moulton and Liothrips reynvaanae Priesner are considered new synonyms of Liothrips pallipes (Karny). Doubts are expressed about the significance of several further described species, and an identification key is provided to nine putative species. Despite the number of Liothrips species described from Piper, there is little evidence of thrips radiation on this plant genus, and the two most common species of the genus on Piper are probably not closely related.